PERLINDUNGAN HUKUM TERHADAP CUSTOMER OJEK ONLINE DALAM KASUS TINDAK PIDANA KEKERASAN SEKSUAL (STUDI KASUS DI KOTA DENPASAR) - Marion Yohanes Talan; Ni Putu Noni Suharyanti (Jurnal Hukum Mahasiswa, 2023)
The development of information technology has been utilized by business actors such as Gojek in developing online application-based transportation, offering various features that make it easier for consumers in every service offered. However, of all the advantages offered, it still has disadvantages that can be detrimental to consumers, such as the behavior of drivers who are impolite and sexually harass consumers. The aims of this study were 1) to find out the legal protection for online motorcycle taxi customers as victims of sexual harassment in online transportation in Denpasar City and 2) to find out the obstacles in legal protection for online motorcycle taxi customers as victims of criminal acts of sexual harassment in online transportation in Denpasar City. The research method used is an empirical research method with a case approach. The results are, 1) Legal protection for online motorcycle taxi customers as victims of criminal acts of sexual harassment in online transportation in Denpasar City, which are commonly provided, include the following: Restitution, Medical Assistance and Psycho-Social Rehabilitation Assistance, Protection from the Family, Protection from the Community , and 2) Obstacles in legal protection of online motorcycle taxi customers as victims of criminal acts of sexual harassment in online transportationin Denpasar City, there are factors that hinder them including: 1) The legal factor itself, 2) the law enforcement factor, 3) the factor Facilities and Facilities, 4) Community Factors, 5) Cultural Factors.